Natural History of Diabetic Retinopathy Through Retrospective Analysis in Type 2 Diabetic Patients—An Exploratory Study - Gupta, Mehak; Singh, Amarjeet; Duggal, Mona; Singh, Ramandeep; Bhadada, Sanjay; Khanna, Poonam (Frontiers in Public Health, 2021)
Background: Diabetic retinopathy (DR) is a common complication associated with diabetes mellitus (DM) presented by blindness and visual impairment, posing an economic healthcare burden. Methods: Retrospective medical records of 170 patients aged >20 years with the confirmed complication of DR were analysed using a structured questionnaire. Results: The results of the present study showed the history of DR, with mild Non-Proliferative DR (NPDR), with moderate NPDR, severe NPDR and proliferative DR were found in 13.5%, 5.9%, 37.1%, 25.3% and 21.8% respectively along with comorbidities in 81.8% patients. Conclusions: The study revealed and concluded that adherence to the prescribed regimen of management is important for which, patient’s education is the key which was lacking